About joint session of Scientists counsel of Burdenko Neurosurgery Institute of RAMS (Moscow) and Romodanov Neurosurgery Institute of AMSU (Kiev), devoted to 100 year from the birthday of the academician A.I.Arutiunov - Zozulya, Yu. A.; Sapon, N. A. (Ukrainian Neurosurgical Journal)
No abstract.